Patterns and determinants of open defecation among urban people - Yulyani, Vera; Febriani, Christin Angelina; Mohd Sham, Shaharuddin; Hermawan, Dessy (Universitas Indonesia, 2021)
At the present time, an estimated of 673 million people defecate in the open space, not in private. Indonesia is a densely populated country with a lot of open defecation (OD) both in urban (37%) and rural areas (43%). Tanjung Karang Pusat Subdistrict is an area in Bandar Lampung City with the highest percentage of OD practice (45%). This study aimed to explore and explain the patterns and determinants of OD among urban people in the Tanjung Karang Pusat Subdistrict in- volving 377 respondents for quantitative analysis. Quantitative data were analyzed using the chi square and regression analysis. After controlling the economic status and education level variables, the data revealed that urban communities were still practicing OD (23.3%) with land ownership, latrine ownership, conative attitude, and occupation as influential factors. Statistical test results showed that the most influential factor in the behavior of OD in the community was latrine ownership (p-value <0.001, OR adj = 58.2). These findings suggested that stakeholders must take action on landowners who do not allow sanitation facilities to be built on their land.